2021
DOI: 10.1038/s41598-021-97150-5
|View full text |Cite
|
Sign up to set email alerts
|

Full-field MRI measurements of in-vivo positional brain shift reveal the significance of intra-cranial geometry and head orientation for stereotactic surgery

Abstract: Positional brain shift (PBS), the sagging of the brain under the effect of gravity, is comparable in magnitude to the margin of error for the success of stereotactic interventions ($$\sim $$ ∼  1 mm). This non-uniform shift due to slight differences in head orientation can lead to a significant discrepancy between the planned and the actual location of surgical targets. Accurate in-vivo measurements of this complex deformation are critical for the design and validation of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 72 publications
0
38
0
Order By: Relevance
“…If the guiding coordinates are generated by an MRI done in supine position, the brain will move slightly away from those coordinates, if the patient is placed into a different position for surgery. This was confirmed by studying 11 health young adult volunteers, who were specifically moved from supine position to prone, and back again [ 4 ]. The head and body rotation studied by the British investigators was essentially identical to that utilized by the Tunisian Investigators in their study.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…If the guiding coordinates are generated by an MRI done in supine position, the brain will move slightly away from those coordinates, if the patient is placed into a different position for surgery. This was confirmed by studying 11 health young adult volunteers, who were specifically moved from supine position to prone, and back again [ 4 ]. The head and body rotation studied by the British investigators was essentially identical to that utilized by the Tunisian Investigators in their study.…”
mentioning
confidence: 90%
“…Part of the answer to this apparent discrepancy may be revealed by a group of British investigators who recently reported [ 4 ] that “positional brain shift,” the sagging of the brain under the effect of gravity, is significant, relative to the specific geometric coordinates generated by magnetic resonance imaging (MRI) for the purpose of guiding stereotactic surgery. If the guiding coordinates are generated by an MRI done in supine position, the brain will move slightly away from those coordinates, if the patient is placed into a different position for surgery.…”
mentioning
confidence: 99%
See 3 more Smart Citations